Use of ionized monocalcium phosphate and enameline derivatives to reduce dentin hypersensitivity after periondontal therapy = Uso de Fostato Monocálcio y derivados en Enamelina para reducir la hipersensibilidad dentaria después de terapia periodontal - Martínez Aguilar, Víctor Manuel
This study aimed to evaluate the effectiveness of using an ionized monocalcium phosphate and enamelin derivatives (IMP+ED) based mouthwash for the treatment of dentin hypersensitivity (DH) after scaling and root planing (SRP). 47 patients who reported DH after SRP treatment were included in this prospective cohort study. The Schiff Cold Air Sensitivity Scale (SCASS) was applied to classify their degree of pain in mild, moderate or intense at two times: after SRP (T0), and after one month of using a IMP+ED-based mouthwash (T1). The McNemar-Bowker test was used to compare the correlated proportions between both times (p<0.05). After the SRP therapy (T0), all the sample members reported pain distributed in the following manner: 12.8% were mild, 27.6% moderate, and 59.6% intense. At one month since treatment and with the use of the IMP+ED-based mouthwash (T1), the distribution of pain levels changed to 83% mild, 12.8% moderate, and 4.3% intense, this change was statistically significant (p<0.001). IMP+ED-based mouthwash produces a positive effect in reducing painful responses caused by exposure of the dentin tubules to the oral environment after SRP therapy.